The Interplay among Self-efficacy, Perceptions of Instructional Supervision, and Teaching Performance: A Case of Iranian EFL Teachers - Afsaneh Baharloo; Saeed Mehrpour (Journal of Modern Research in English Language Studies)
This study aimed to investigate the relationship between language teachers' perception of instructional supervision and their self-efficacy. In addition, it intended to delve into the interplay among self-efficacy, perception of supervision, and teaching performance of Iranian EFL teachers. Employing a mixed-method design, the researchers collected the data, using questionnaires and observation. A total number of 116 EFL instructors teaching at language institutes in Shiraz participated in the quantitative phase of the study. Making use of purposive sampling, the researchers asked 46 of the participants to cooperate in the second phase of the study in which data was collected through classroom observations. In order to analyze the collected data, the researchers utilized descriptive statistics, Cronbach's alpha, Pearson correlation, multiple regression analysis, and code-recode agreement techniques. The findings of the study revealed a significant positive relationship between teachers' self-efficacy and their perception of instructional supervision (r = 0.22, p<0.05). Moreover, the participants' teaching performance was significantly correlated with their self-efficacy (r = 0.64, p<0.05) and their perception of supervision (r=0.10, p<0.05). In addition, further investigation of the data revealed that teachers' self-efficacy was the only variable that made a significant unique contribution to their teaching performance (Beta = 0.43, p<0.05).